Pollen analysis on spotted hyaena (Crocuta crocuta) coprolites from the Late Pleistocene site of Buca della Jena, Southern Tuscany (Roselle, Grosseto, Italy). - Francesco Ciani; Omar Cirilli; Luca Pandolfi; Saverio Bartolini Lucenti; Andrea Savorelli; Andrea Sforzi; Lorenzo Rook; Marta Mariotti Lippi (2019)
Pollen studies in fossil faecal remains may provide significant palaeoclimatic, palaeovegetational and palaeoethnological information. These data can be decisive where other substrates are not available for pollen analysis. Coprolites, thanks to their hardness, can preserve pollen grains for a long time, isolating them and preventing exine oxidation. It is known that pollen is incorporated into coprolites in different ways: by the ingestion with food or water, by the licking of the fur. Noticeable pollen amount is found when the diet includes flowering plants. Pollen analysis was lead on two coprolites of spotted hyaena Crocuta crocuta found in the site of Buca della Jena (Roselle, GR) in order to reconstruct the local vegetation surrounding the hyaenas den. The samples were taken from the center of each coprolite and treated following the standard procedure. The analysis revealed a rather good pollen concentration in both the coprolites, which also displayed similar pollen spectra. Almost all the pollen grains belonged to herbaceous plants. The most represented taxa were Plantago, Chenopodiaceae and Poaceae, the two lasts with different morphotypes. Urticaceae and Lamiaceae also showed noticeable percentages. The fossil assemblage at Buca della Jena includes the following species: Crocuta crocuta, Canis Lupus, Vulpes vulpes, Ursus arctos, Equus ferus, Cervus elaphus, Rupicapra rupicapra, Arvicola amphibius, Microtus (Microtus) arvalis, Lepus sp. According to the faunal record, the presence of Rupicapra rupicapra and Microtus arvalis suggest a relatively cold environment in the surrounding of BDJ, whereas the occurrence of Arvicola amphibious and Crocuta crocuta indicates an age referable to the Late Pleistocene, older than ca. 31 ka, last occurrence of the spotted hyaena in Italy. The pollen results hint the presence of an extensive grassland characterized by taxa which are common in the steppe vegetation. This scenario may describe the environment visited by the hyenas during their feeding activity in one or ...